Hybrid battery-supercapacitor mathematical modeling for PV application using Matlab/Simulink - Argyrou, Maria C.; Christodoulides, Paul; Marouchos, Christos; Kalogirou, Soteris A. (My University, 2018)
Energy storage plays an important role in the renewable energy sources integration. Additionally, hybrid energy storage can be integrated into various systems to achieve different applications. Specifically, the combination of high energy and power rating, increased life cycle, duration of discharge period and other features may not be satisfied by the single storage technology. There are several storage technologies that may be used in a photovoltaic (PV) system. This paper focuses on the mathematical modeling of the hybrid battery-supercapacitor storage system. The hybrid storage combines the advantages of both battery and supercapacitor storage. Also, supercapacitors can reduce stresses on battery storage and thus extend their battery life. The proposed mathematical model is implemented using Matlab/Simulink. Regarding the supercapacitor equivalent circuit, the two branches model is examined. For the lithium-ion battery storage model, a dual polarization model with two parallel RC networks is studied. The next step is to integrate the hybrid battery-supercapacitor storage into a grid-connected PV system.
Keywords: Battery; Hybrid energy storage; Lithium-ion; Modeling; Photovoltaics; Simulink; Supercapacitors